Exploring behavior, motivation, and barriers to exercise in Parkinson disease - Allison M. Haussler; Sidney T. Baudendistel; Lauren E. Tueth; Gammon M. Earhart (Clinical Parkinsonism & Related Disorders, 2025)
Introduction: Despite extensive evidence for its numerous benefits, many people with Parkinson’s disease (PwPD) do not meet recommended exercise guidelines. Past work investigated motivators and barriers to exercise generally. The purpose of this study was to synthesize motivator and barrier data to individual forms of exercise to better assess what participants are willing and able to do. Methods: PwPD were recruited to complete a remote survey, selecting exercise forms they engage in, are unwilling to engage in, and rate their level of agreement with pre-determined motivator and barrier statements. Specific exercises and motivator and barrier statements were adapted from the literature; however, participants were able to respond with an exercise or motivator/barrier not listed. Results: PwPD (n = 147) completed the survey and were included in analyses. Eighty-eight percent of participants agreed exercise is important for managing PD symptoms. Walking was the most popular exercise individuals engaged in (n = 106); dance was the least (n = 4). Belief that exercise was beneficial for general health was the top motivator; dislike and fear of falling were top barriers. Belief that there is scientific evidence was the least common motivator across exercises, except for boxing. Conclusion: Clinicians can utilize these results to educate PwPD on the importance of exercise for fall prevention and other aspects of care. Additionally, scientific evidence may best be disseminated in clinician-patient interactions, as “recommendation from a clinician” was a high ranked motivator. It is important to assess motivators and barriers to individual exercise forms to develop more personal, effective exercise plans.